2019
DOI: 10.1021/acs.jafc.9b01829
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Biofortification of Wheat with Zinc, Iodine, Selenium, and Iron through Foliar Treatment of a Micronutrient Cocktail in Six Countries

Abstract: Field experiments were conducted on wheat to study the effects of foliar-applied iodine(I) alone, Zn (zinc) alone, and a micronutrient cocktail solution containing I, Zn, Se (selenium), and Fe (iron) on grain yield and grain concentrations of micronutrients. Plants were grown over 2 years in China, India, Mexico, Pakistan, South Africa, and Turkey. Grain-Zn was increased from 28.6 mg kg −1 to 46.0 mg −1 kg with Zn-spray and 47.1 mg −1 kg with micronutrient cocktail spray. Foliar-applied I and micronutrient coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
91
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 52 publications
11
91
0
Order By: Relevance
“…* = significantly different at P < 0.05. tended to increase grain Zn ( Table 5). A very similar finding has been also reported in field studies conducted on wheat grown in six countries (Zou et al, 2019). The lack of antagonism between Zn and Se (Mangueze et al, 2018) or Fe and Zn (Wei et al, 2012) has been also shown in rice when these micronutrients are sprayed together in the same spray solution.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…* = significantly different at P < 0.05. tended to increase grain Zn ( Table 5). A very similar finding has been also reported in field studies conducted on wheat grown in six countries (Zou et al, 2019). The lack of antagonism between Zn and Se (Mangueze et al, 2018) or Fe and Zn (Wei et al, 2012) has been also shown in rice when these micronutrients are sprayed together in the same spray solution.…”
Section: Discussionsupporting
confidence: 84%
“…To our knowledge, this study is the first one showing a very positive effect of combined foliar sprays of Zn, I and Se on grain concentrations of these micronutrients in many rice cultivars grown in several countries. A similar positive effect of the foliar applied micronutrient cocktail solution on grain concentrations of the micronutrients has been also shown in wheat grown in 6 different countries (Zou et al, 2019). In contrast to Zn, I and Se, the concentration of Fe in grain was not affected with the spray of the micronutrient cocktail ( Table 7).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…When soils are deficient in several micronutrients, a simultaneous biofortification might be more effective and profitable for farmers, as previously suggested by Zou et al (2019) in other crops, such as wheat. In peas, the combined Se and Zn biofortification has demonstrated to be effective in the increase of Se and Zn in the grain under greenhouse conditions (Poblaciones and Rengel 2017).…”
Section: Introductionmentioning
confidence: 76%
“…Finally regarding Fe, the foliar applications containing Zn caused a clear decrease in the Fe concentration. Iron-zinc interaction seems to be complex as both positive and negative (even neutral) effects between them can be found in the literature (Saha et al 2017;Zou et al 2019). Therefore in general terms, the Zn application had a negative influence in the concentration in forage of Mg, Ca, and Fe, all of them are essential nutrients for livestock, but in any case, even in the more severe diminutions, the concentration levels of those three minerals were above the threshold of recommended values (Suttle 2010).…”
Section: Discussionmentioning
confidence: 99%